2014
DOI: 10.1302/2046-3758.39.2000294
|View full text |Cite
|
Sign up to set email alerts
|

T lymphocytes are not required for the development of fatty degeneration after rotator cuff tear

Abstract: Objectives Rotator cuff tears are among the most common and debilitating upper extremity injuries. Chronic cuff tears result in atrophy and an infiltration of fat into the muscle, a condition commonly referred to as ‘fatty degeneration’. While stem cell therapies hold promise for the treatment of cuff tears, a suitable immunodeficient animal model that could be used to study human or other xenograft-based therapies for the treatment of rotator cuff injuries had not previously been identified.Methods A full-thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 52 publications
2
13
0
Order By: Relevance
“…Despite the location of SVFCs within adipose tissue, we did not find any human β2M or Alu + adipocytes within torn rotator cuff muscles, and we did not detect any changes in total lipid content between groups. The abundance of total triglyceride content of muscles in the current study is consistent with levels observed in previous rat studies [8, 9]. Although there were no differences between groups with regards to lipid content, there was a trend towards an improvement in muscle fiber sF o production in the 3×10 6 cell group, indicating that the treatment with SVFCs did not exacerbate fatty degeneration within these muscles.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Despite the location of SVFCs within adipose tissue, we did not find any human β2M or Alu + adipocytes within torn rotator cuff muscles, and we did not detect any changes in total lipid content between groups. The abundance of total triglyceride content of muscles in the current study is consistent with levels observed in previous rat studies [8, 9]. Although there were no differences between groups with regards to lipid content, there was a trend towards an improvement in muscle fiber sF o production in the 3×10 6 cell group, indicating that the treatment with SVFCs did not exacerbate fatty degeneration within these muscles.…”
Section: Discussionsupporting
confidence: 91%
“…Chronic fibrosis after rotator cuff tear leads to increased muscle stiffness and tension at the repair site [4], and along with the poor quality of the muscle due to atrophy and fatty infiltration [8], the potential for healing of torn rotator cuff muscles even after repair remains low. SVFC transplantation has been associated with a reduction in fibrosis and improved regeneration in other tissue injury and disease models, such as liver injury [13], Peyronie's disease [14], myocardial infarctions [15], and Dupuytren's disease [16], and supports our finding of reduced fibrosis after rotator cuff tear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations